2017
DOI: 10.1039/c6ra27633d
|View full text |Cite
|
Sign up to set email alerts
|

Computational prediction and experimental confirmation of rhombohedral structures in Bi1.5CdM1.5O7 (M = Nb, Ta) pyrochlores

Abstract: We present theoretical predictions for the electronic band and crystal structure of Bi1.5CdM1.5O7 (M = Nb, Ta) using DFT. The DFT calculated band gaps are in very good agreement with optical band gaps estimated from UV-Vis spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Concentration driven structural distortion and phase transition behaviour is usually associated with a peak splitting and broadening effects. These phenomenon has been reported to study the ferroelectric and electromechanical properties of bismuth based dielectric material 32,33 . In the present system the transformation from cubic to pseudo-cubic/rhombohedral structural is mainly observed in the region of {111, 311, 222} diffraction peaks.…”
Section: Resultsmentioning
confidence: 91%
“…Concentration driven structural distortion and phase transition behaviour is usually associated with a peak splitting and broadening effects. These phenomenon has been reported to study the ferroelectric and electromechanical properties of bismuth based dielectric material 32,33 . In the present system the transformation from cubic to pseudo-cubic/rhombohedral structural is mainly observed in the region of {111, 311, 222} diffraction peaks.…”
Section: Resultsmentioning
confidence: 91%
“…Our approach to crystal structure determination in this work is similar in philosophy to an earlier study on precise determination of the site occupancy, structure, and space group for bismuth-based pyrochlore photocatalysts. 25 In the pyrochlore series, substitution of a larger ion ( e.g ., Cd) can lead to changes in symmetry from cubic to rhombohedral with consequent implications for experimental and theoretical determinations of band gap values. 25 In this study, clarity on the structure and composition of the KVP phase influences our models on potassium transport in electrode materials for batteries.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In the pyrochlore series, substitution of a larger ion ( e.g ., Cd) can lead to changes in symmetry from cubic to rhombohedral with consequent implications for experimental and theoretical determinations of band gap values. 25 In this study, clarity on the structure and composition of the KVP phase influences our models on potassium transport in electrode materials for batteries. We elaborate below on synthesis conditions for the optimum production of K 3 V 3 (PO 4 ) 4 ·H 2 O, key influences on ion transport, and spectroscopic interpretation of this important phase.…”
Section: Discussionmentioning
confidence: 99%
“…(and citations in there), the authors demonstrated that although the substituted pyrochlore structure for certain substitutions may appear cubic in XRD, it is likely already slightly distorted towards structures with reduced symmetry. [13] This work is a continuation of the systematic study of defect pyrochlore with the composition ABB 0 O 6 , where А-K + , Rb + , and Cs + ; B-Ta + , Nb 5+ , and Sb 5+ ; B 0 -Te 6+ and W 6+ . [14][15][16][17] We present results from Raman scattering studies at high pressures, on the ionic conducting system KNbTeO 6 (KNT), as well as results of lattice dynamics (LD) calculations for this compound.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, in the work of Perenlei et al (and citations in there), the authors demonstrated that although the substituted pyrochlore structure for certain substitutions may appear cubic in XRD, it is likely already slightly distorted towards structures with reduced symmetry. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%